Otimização da eficiência energética em redes operando com tsch: avaliação analítica de uma implementação prática. - Sordi, Marcos Antonio de (2019)
The IEEE 802.15.4-2015 standard defines a number of Medium Access Control (MAC) layer protocols for low power wireless communications, which is desirable for constrained Internet of Things (IoT) devices. Originally defined in IEEE 802.15.4e amendment, the Time Slotted Channel Hopping (TSCH) is recently attracting the attention from the research community, due to its reduced contention (time scheduling) and robustness (channel hopping). However, the TSCH needs a certain level of synchronization between the nodes, which can lead to a higher energy consumption. A guard time mechanism is implemented to ensure that the nodes will hear the frames even if they are not perfectly synchronized. In this work, we implement the Guard Beacon strategy, aiming to reduce the guard time, and present a realistic energy consumption model for a Contiki OS-based TSCH networks. The analytical values have a good match with the results obtained from the Contiki Powertrace Tool running on a real TSCH network and demonstrate that the proposed scheme can reduce the overall power consumption of each node by 13.05%.